Transformations of Transitive Verbs in Qira’at al-‘Asyrah of Surah al-Baqarah: A Semantic Study and Its Influence on Arabic Language Learning: تحوّلات الأفعال المتعدّية في القراءات العشر في سورة البقرة: دراسة دلاليّة وأثرها في تعليم اللغة العربية - Taufik Amin Nur Wijaya (UIN Raden Mas Said Surakarta, 2026)
The revelation of the Qur’an in sab’atu achruf is one of the manifestations of i’jaz al-Qur’an. It gave rise to the diversity of qira’at, enriching the meanings contained within a single lafdzul ayah, while remaining authentically preserved through reliable transmission. This study aims to examine the variations of Qira’at al-‘Asyrah in transitive verbs found in surah al-Baqarah, as well as their implications for morphological, syntactic, and semantic aspects. Furthermore, it explores a qualitative approach using a descriptive analytical method through library research. An-Nasyru by Ibn al Jazari serves as the primary data source, supported by other classical books. Data were analyzed using the content analysis technique through the processes of selecting and classifying qira’at variants based on the types of linguistic changes. The findings indicate that differences in qira’at produce systemic variations in ta’diyah, either through transformations between mujarrad and mazid or through shifts in the grammatical functions of fa’il and maf’ul bih. These variations do not result in semantic contradictions, rather they broaden and deepen the contextual semantic of the verses. The finding confirms that qira’at constitutes a coherent normative linguistic system. Pedagogically, this study shows that qira’at can be utilized as an authentic data source for Arabic language learning by integrating morphological and syntactic analysis as well as semantic changes based on Qur’anic texts.